2008
DOI: 10.1007/s12311-008-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Acquisition in the Cerebellum: An fMRI Study of Cerebrocerebellar Interaction During Visual Duration Discrimination

Abstract: It has been suggested that the cerebellum participates in diverse neuropsychological functions by adjusting the sensory information acquired for the connected brain regions to support its processing capabilities. Nevertheless, the knowledge of how the cerebellum is modulated by the sensory information is far from clear. Function magnetic resonance imaging was exploited to investigate how the cerebellum activity and cerebrocerebellum interaction can be affected by the interaction between visual size and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…More recently, the cerebellum has also been implicated in social, cognitive, and emotional functions (Bauman and Kemper 2005). Shih et al (2008) showed that the cerebellum plays a critical role in sensory acquisition and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the cerebellum has also been implicated in social, cognitive, and emotional functions (Bauman and Kemper 2005). Shih et al (2008) showed that the cerebellum plays a critical role in sensory acquisition and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that, due to its uniform neuro-architecture with closed input–output loops that connect cerebellum and cerebrum (Middleton and Strick 1994; Strick et al 2009), the cerebellum also possesses uniform processing habits to enable overarching, domain-independent functions such as monitoring, coordination, and timing (Strick et al 2009). Along these lines, the cerebellum may also provide other basic functions such as sensory acquisition (Gao et al 1996; Bower 1997; Shih et al 2009), internal modelling/error correction (Wolpert et al 1998; Ito 2008), performance monitoring (Peterburs and Desmond 2016), and sequence detection (Braitenberg et al 1997; Molinari et al 2008; Leggio and Molinari 2015; Tedesco et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Put another way, the cerebellum may be more "motor for sensory sake," than "sensory for motors sake" . Evidence consistent with such a role has now been obtained from human subjects performing tactile (Gao et al 1996), olfactory (Sobel et al 1998), visual (Baumann and Mattingley 2010;Shih et al 2009Shih et al , 2010, and auditory (Petacchi et al 2005(Petacchi et al , 2011 sensory discriminations.…”
Section: A New Cortical Computational Algorithmmentioning
confidence: 67%